Quantitative analysis of endobronchial elastography combined with serum tumour markers of lung cancer in the diagnosis of benign and malignant mediastinal and hilar lymph nodes - Zhen Wang; Peng Li; Jiayu Bai; Yujia Liu; Guangyu Jiao (Frontiers Media S.A., 2023)
Purpose: In malignant tumours, elastography and serum tumour markers have shown high diagnostic efficacy. Therefore, we aimed to quantitatively analyse the results of endobronchial elastography combined with serum tumour markers of lung cancer to accurately distinguish benign and malignant mediastinal and hilar lymph nodes.Methods: Data of patients who underwent endobronchial ultrasound-guided transbronchial needle aspiration for mediastinal lymph node enlargement in our hospital between January 2018 and August 2022 were retrospectively collected. The characteristics of quantitative elastography and serum tumour markers were evaluated.Results: We enrolled 197 patients (273 lymph nodes). In the differential diagnosis of benign and malignant mediastinal and hilar lymph nodes, the stiffness area ratio (SAR), strain ratio (SR), and strain rate in lymph nodes were significant, among which SAR had the highest diagnostic value (cut-off value, 0.409). The combination of the four tumour markers had a high diagnostic value (AUC, 0.886). Three types of quantitative elastography indices combined with serum tumour markers for lung cancer showed a higher diagnostic value (AUC, 0.930; sensitivity, 83.5%; specificity, 89.3%; positive predictive value, 88.1%; negative predictive value, 85%) (p < 0.05). In the differential diagnosis of pathological types of lung cancer, different quantitative elastography indicators and serum tumour markers for lung cancer have different diagnostic significance for the differential diagnosis of lung cancer pathological types.Conclusion: The quantitative analysis of endobronchial ultrasound elastography combined with tumour markers can improve the diagnosis rate of benign and malignant mediastinal and hilar lymph nodes, help guide the puncture of false negative lymph nodes, and reduce the misdiagnosis rate.